229k views
3 votes
Help me solve this problem:

2y(6 - 1)2 = -200

In other words it is 2y times 6 - 1 by exponent 2 = -200

2 Answers

3 votes

Solve: 2y(6 - 1)^2 = - 200



Simplify both sides of equation:


50y = - 200



Divide both sides by 50


50y/50 = - 200/50


y = - 4




Answer: y = - 4






Hope that helps!!!! (Answer: y = - 4)

User Dzl
by
6.0k points
6 votes

So firstly, solve the parentheses, then combine it with the exponent. Your equation will look like this:
2y*25=-200 .


Next, divide both sides by 25, and your equation should be
2y=-8


Lastly, divide by 2, and your answer should be
y=-4

User Alexis Peters
by
5.4k points